Effect of Integrated Pest Management Training on Ugandan Small-Scale Farmers. (11th April 2017) - Clausen, Anna Sabine; Jørs, Erik; Atuhaire, Aggrey; Thomsen, Jane Frølund
Small-scale farmers in developing countries use hazardous pesticides taking few or no safety measures. Farmer field schools (FFSs) teaching integrated pest management (IPM) have been shown to reduce pesticide use among trained farmers. This cross-sectional study compares pesticide-related knowledge, attitude, practice (KAP), potential exposure, and self-reported poisoning symptoms among 35 FFS farmers, 44 neighboring farmers, and 35 control farmers after an IPM intervention in Uganda (2011-2012). The FFS farmers were encouraged to teach their neighboring farmers. Data were based on standardized interviews and were analyzed using a linear trend test and logistic regression. The results showed that FFS and neighboring farmers used significantly fewer pesticide applications ( P = .021) and used more safety measures. No differences were found on the hazardousness of pesticides used or self-reported symptoms. The study supports IPM as a method to reduce pesticide use and potential exposure and to improve pesticide-related KAP among small-scale farmers in developing countries.